Genetic-local hybrid optimizer for solving advance layout problem - Taha, Imad; Ibrahim Habra, Hind Saleem (Al Rafidain University College, 2006)
Advance Layout problem(ALP) is used to search for an optimal layout of machines. This research describes a novel method, based on genetic algorithms(GA) to solve the machine layout problem, where developing machine layout is an important step designing manufacturing, renovation of factories, distribution centers, hospitals, banks, department stores, military supply, depots, universities, etc. The research studies the problem of adding the heterogeneous objects, continuous placement in the general spatial layout problem. Results are achieved through the use of local optimizer, separation algorithm with genetic algorithm also called hybrid simple genetic. Results show the potentiality of the proposed algorithm in solving the problem and outperforming previous algorithms.